Involving native speakers in oral corrective focused grammar feedback while conversing: an activity theory perspective. Issue 5 (3rd September 2022) - Reynolds, Barry Lee; Teng, Mark Feng
ABSTRACT: Higher education institutions often pair native speakers with English as a second and foreign language learners to encourage oral conversation practice. Born out of such circumstances, the current investigation, drawing upon the activity theory perspective, examined the plausibility of native-speaking conversation partners providing oral corrective focused grammar feedback. Two advanced South Korean male English learners were recruited as case studies – one received explicit oral corrective focused grammar feedback on plural noun errors while the other did not receive corrective feedback. Results of the learners' grammatical accuracy during four conversation sessions, stimulated recalls, and the native speaker conversation partner's reflection reports were analysed and discussed. Providing oral corrective focused feedback resulted in a decrease in language output and grammar accuracy while increasing languaging. The conversation activities were driven and defined by the learners' motives, and their motives were shaped and influenced by the sociocultural conditions that the students had experienced. The learners formed different stances and patterns of interactions while encountering rules and division of labour in the conversation activity with the native speaker. The levels of motives and agency were not stagnant but fluctuated over time because of the dynamic influence of internal and external factors related to the conversation activity. Suggestions for conversation partner training are provided and the practicalities of native-speaking conversation partners providing oral corrective focused grammar feedback are discussed.